Favorable outcome with direct‐acting antiviral treatment in hepatitis C patients coinfected with HIV. Issue 9 (17th June 2019) - Ishida, Hisashi; Ishihara, Akio; Tanaka, Satoshi; Iwasaki, Tetsuya; Hasegawa, Hiroko; Akasaka, Tomofumi; Sakakibara, Yuko; Nakazuru, Shoichi; Uehira, Tomoko; Shirasaka, Takuma; Mita, Eiji
Abstract : Aim: To investigate the efficacy and safety of all‐oral direct‐acting antiviral treatments in patients coinfected with hepatitis C virus (HCV) and HIV. Methods: In all, 35 patients with HCV/HIV coinfection (22 patients with HCV genotype 1 infection, 6 with genotype 2, and 7 with genotype 3) were treated with sofosbuvir and ledipasvir (for genotype 1 patients) or sofosbuvir and ribavirin (for genotypes 2 and 3). Sustained virological response (SVR) at 24 weeks after end of treatment and adverse events were assessed. Results: The overall SVR rate was 91.4% (32/35). One patient with genotype 1 infection discontinued treatment on day 2 due to severe headache, which subsided after the cessation of medication; all other patients completed their treatment without severe adverse events. Two patients who had a relapse of HCV were infected with a genotype 3 strain. We observed hyperbilirubinemia in a patient with genotype 3, who was under antiretroviral therapy including atazanavir. He completed the treatment and achieved SVR. Conclusion: Direct‐acting antiviral treatment for patients coinfected with HCV/HIV is as effective as in patients infected only with HCV. It was generally well tolerated, except in one patient who discontinued the treatment due to severe headache.